Microbial contamination in smoked tuna at traditional market of Tobelo, North Halmahera, Indonesia - Febrina Olivia Akerina (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2018)
Smoked tuna is one of traditional fisheries product in Tobelo, North Halmahera. Tobelos people like this product because of its smoke taste. In Tobelo, there are many producer who sell this product, but information about its quality was unknown. In this research, the researcher wants to know about microbiology aspect of smoked tuna from three traditional market in Tobelo. The result of this research showed that Total Plate Count (TPC) value was from 7,5x1015,35x102 APM/g; smoked tuna from modern Market showed the highest Staphulococcus sp. colony at 1,3x103 CFU/g. colony of Salmonella sp. showed negative value for three different market. The highest fungy colony was 2,5x101 CFU/g from Gotong royong Market, for Escherichia coli analysis, smoked tuna from Gotong Royong Market showed high value at 23 CFU/g, it was exceed Indonesia National Standard.